2003
DOI: 10.1111/j.1553-2712.2003.tb00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pain Is Underassessed in Out‐of‐hospital Emergencies

Abstract: EMS providers significantly underestimate their patients' pain severity. EMS providers should be more attentive to their patients' complaints and comfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 19 publications
0
22
0
3
Order By: Relevance
“…Research indicates that healthcare providers – nurses in particular – are prone to underestimate the severity of patient pain compared to self-report, and that there is variability in pain ratings between and within provider types (Choiniere et al, 1990; Davoudi et al, 2008; Green et al, 2001; Green and Wheeler, 2003; Luger et al, 2003; Sloman et al, 2005). Relatively little has been published concerning the accuracy of nurses’ assessment of patient emotional status in general and in the context of pain in particular.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research indicates that healthcare providers – nurses in particular – are prone to underestimate the severity of patient pain compared to self-report, and that there is variability in pain ratings between and within provider types (Choiniere et al, 1990; Davoudi et al, 2008; Green et al, 2001; Green and Wheeler, 2003; Luger et al, 2003; Sloman et al, 2005). Relatively little has been published concerning the accuracy of nurses’ assessment of patient emotional status in general and in the context of pain in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who are female (see reviews by Kamath and O'Connor, 2011 and LeResche, 2011), racial/ethnic minority (see reviews by Kamath and O'Connor, 2011 and Mossey, 2011), and elderly (Auret and Schug, 2005; Heins et al, 2006; Horgas and Elliott, 2004; Iyer, 2010) are at increased risk for sub-optimal pain care. These factors may also play a role in the assessment of patient mood; however, this has received little empirical attention to date.…”
Section: Introductionmentioning
confidence: 99%
“…Significant deficiencies in acute pain management in emergency medicine have been identified. Several studies reported an underestimation of pain by (emergency) physicians and nurses (Luger et al, 2003) and deficiencies in pre-hospital pain management (Abbuhl and Reed, 2003;Hennes et al, 2005;Berben et al, 2011a). Similar results are reported in the ED (Todd et al, 2007;Berben et al, 2008).…”
Section: Introductionmentioning
confidence: 66%
“…Die kli ni sche Re le vanz der vor lie genden Er geb nis se liegt da rin, dass Fehl urtei le des be han deln den Arz tes zu ei ner the ra peu ti schen Über-oder Un ter ver sorgung füh ren kön nen [8,18]. Dies ist ins beson de re bei Pa ti en ten zu er war ten, de ren Schmer zen vom Arzt nicht er kannt werden, da sie ent we der von ei ner an ge messe nen the ra peu ti schen Ver sor gung aus geschlos sen wer den oder eine Ten denz zum "doc tor shop ping" ent wi ckeln, weil sie sich von ih rem be han deln den Arzt un ver standen füh len.…”
Section: Be Wer Tung Und In Ter Pre Ta Ti On Der Er Geb Nis Seunclassified
“…Sehr häu fig werden Schmer zen des Pa ti en ten ge ra de vom me di zi ni schen Per so nal un ter schätzt [25]. Die se Ur teil ab wei chun gen sind sys te matisch: Sie tre ten un ab hän gig von der beur teil ten Pa ti en ten po pu la ti on [2,5,17,24,26] und dem ver wen de ten Ska len typ auf [14,18]. Eine Viel zahl von Fak to ren begüns tigt einen Bias des be han deln den Arztes im Sin ne ei nes "un der re por ting" von Schmer zen.…”
unclassified